Cardiovascular Fitness Assessment of Medical Students at Patan Academy of Health Sciences, Lalitpur, Nepal - Shakya, Binnam; Byanju, Jayandra; Maharjan, Sanjay; Bhaila, Archana (Annapurna Journal of Health Sciences, 2023)
Introduction: Despite of being aware of the fact that medical students should be healthy and have good physical fitness for better productivity, have difficulty in balancing their studies and physical fitness. Three minute step test is one of the widely used methods to assess the cardiovascular fitness after performing the submaximal exercise. Thus, this study aims to assess the cardiovascular fitness of the medical students by performing a YMCA (Young Men’s Christian Association) 3-minutes step test. Methods: This cross sectional study included 92 medical students of either sex with the age of 18-25 years. The test was performed by stepping up and down on 30 cm bench keeping in time with the beat of the metronome and recovery heart rate was recorded. The cardiovascular fitness was then categorized based on their recovery heart rate. Results: Fitness level of medical students at Patan Academy of Health Sciences was found to be dominantly very poor (Very poor fitness level 43.6%, poor fitness level 29.3%, below average fitness level 9.8%, average fitness level 6.5%, above average fitness level 5.4% and good fitness level 5.4%). Conclusion: The findings of the study remind us about the level of physical activity among the medical students and the need to promote a physically active lifestyle for a positive impact on their health and academic performance.